Relationship between penta-coordinated Al3+ sites in the Al2O3 supports and CH4 combustion activity of Pd/Al2O3 catalysts. Issue 7 (22nd March 2021) - Murata, Kazumasa; Shiotani, Takumi; Ohyama, Junya; Wakabayashi, Ryutaro; Maruoka, Hirokazu; Kimura, Tatsuo; Satsuma, Atsushi
Abstract : Pd/Al2 O3 catalysts were prepared using various Al2 O3 supports with different structural features, revealing a significant insight into the methane (CH4 ) combustion activity of Pd nanoparticles with the fraction of penta-coordinated Al 3+ sites in the Al2 O3 supports. Abstract : Pd/Al2 O3 catalysts were prepared using various Al2 O3 supports with different structural features such as crystalline phase and crystallinity related to Al 3+ coordination, revealing a significant insight into the methane (CH4 ) combustion activity of Pd nanoparticles with the fraction of penta-coordinated Al 3+ sites in the Al2 O3 supports.